Neonatal fungal infections: new strategies in diagnosis - Angelica Dessì (Hygeia Press di Corridori Marinella, 2014)
In Neonatal Intensive Care Unit, fungal sepsis are the third leading cause of late onset sepsis among very low birth weight neonates. Many of biomarkers known are neither sensitive nor specific enough to provide an accurate diagnosis of invasive fungal infections. Indeed even today, the "gold standard" in the diagnosis of neonatal fungal sepsis is positive blood culture. Since neonatal sepsis is a multiorgan disorder that leads to metabolic changes in the organism, new technologies such as metabolomics are becoming a promising method in early diagnosis and are capable of predicting onsets, thus allowing personalized treatment and monitoring of neonatal sepsis. Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou